Identification of multiple species and subpopulations among Australian clinical Sporothrix isolates using whole genome sequencing. (30th November 2018) - New, David; Beukers, Alicia G; Kidd, Sarah E; Merritt, Adam J; Weeks, Kerry; van Hal, Sebastiaan J; Arthur, Ian
Abstract: Whole genome sequencing (WGS) was used to demonstrate the wide genetic variability within Sporothrix schenckii sensu lato and establish that there are two main species of Sporothrix within Australian clinical isolates— S. schenckii sensu stricto and Sporothrix globosa. We also demonstrated southwest Western Australia contained genetically similar S. schenckii ss strains that are distinct from strains isolated in the eastern and northern states of Australia. Some genetic clustering by region was also noted for northern NSW, Queensland, and Northern Territory. Phylogenetic analysis of WGS data provided greater phylogenetic resolution compared to analysis of the calmodulin gene alone.